1995
DOI: 10.1152/ajpgi.1995.268.5.g868
|View full text |Cite
|
Sign up to set email alerts
|

Effects of posture on gastric emptying of nonnutrient liquids and antropyloroduodenal motility

Abstract: The effects of posture on gastric emptying, intragastric distribution, and antropyloroduodenal motility after ingestion of a nonnutrient liquid have been evaluated. In seven healthy volunteers antropyloroduodenal pressures were measured for 30 min after ingestion of 150 ml of normal saline in two different positions: sitting and left lateral. Saline drinks were radiolabeled and ingested both before and after intravenous atropine (4 micrograms/kg). Rates of emptying from both the total (P < 0.05) and the proxim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
37
0
1

Year Published

2006
2006
2011
2011

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 43 publications
(43 citation statements)
references
References 0 publications
5
37
0
1
Order By: Relevance
“…Despite the force of gravity being the same for both kinds of liquids, corresponding studies confirmed this difference [6,7]. Whereas intragastric volume and gravity appear to be the driving forces controlling gastric emptying of nonnutrient liquids [2,5,8], for nutrient liquids, feedback from small intestinal "nutrient" receptors is the decisive factor. These receptors, which are sensitive to, for example, carbohydrates and digestion products of fat, mediate the slowing of gastric emptying [2,4,5,8].…”
Section: Effects Of Posture On the Gastric Residence Time Of Fluids Amentioning
confidence: 94%
See 4 more Smart Citations
“…Despite the force of gravity being the same for both kinds of liquids, corresponding studies confirmed this difference [6,7]. Whereas intragastric volume and gravity appear to be the driving forces controlling gastric emptying of nonnutrient liquids [2,5,8], for nutrient liquids, feedback from small intestinal "nutrient" receptors is the decisive factor. These receptors, which are sensitive to, for example, carbohydrates and digestion products of fat, mediate the slowing of gastric emptying [2,4,5,8].…”
Section: Effects Of Posture On the Gastric Residence Time Of Fluids Amentioning
confidence: 94%
“…This is also reflected in the emptying pattern, which is predominantly linear for nutrient liquids and exponential for nonnutrient ones [2]. Consequently, nutrient liquids are emptied slower, and the process is largely independent of posture [2,5] (see results of Burn-Murdoch et al, Table 1). In terms of the effects of posture on the gastric emptying of solid food, conflicting results have been published.…”
Section: Effects Of Posture On the Gastric Residence Time Of Fluids Amentioning
confidence: 97%
See 3 more Smart Citations